2016
DOI: 10.12806/v15/i3/r3
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Tenets of Military Veterans Working as School Administrators

Abstract: This study investigates the leadership tenets informing veterans' work as school leaders. Drawing on 15 interviews and surveys with military veterans working as educational leaders, the study relies on Stake's (2006) case study method to substantiate assertions that veterans: 1) come into education without the support of a transitional program, 2) are committed to taking care of their people, 3) have a strong belief in service, 4) are influenced by leadership that they have witnessed, and 5) are equipped to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Principals and assistant principals serve vital roles in K-12 educational settings, including influencing school culture, motivating students and teachers, and affecting student academic achievement (Bolles & Patrizio, 2016;Day et al, 2016;Dutta & Sahney, 2016). As critical as principals and assistant principals are, retaining effective administrators has been a challenge.…”
Section: Principal Shortagementioning
confidence: 99%
See 1 more Smart Citation
“…Principals and assistant principals serve vital roles in K-12 educational settings, including influencing school culture, motivating students and teachers, and affecting student academic achievement (Bolles & Patrizio, 2016;Day et al, 2016;Dutta & Sahney, 2016). As critical as principals and assistant principals are, retaining effective administrators has been a challenge.…”
Section: Principal Shortagementioning
confidence: 99%
“…In addition, they had more developed leadership and management skills than teachers who became principals through non-militaryrelated pre-training programs. More recently, Bolles and Patrizio (2016) conducted a multi-case study with 15 military veterans working as educational leaders. Findings indicated that (a) leaders' military and educational experience informed their leadership style, (b) focusing on people was essential, as was (c) having a belief in service, and (d) possessing leadership and accountability (Bolles & Patrizio, 2016).…”
Section: Recruiting Military Veterans For Administrative Positionsmentioning
confidence: 99%